In Vivo Evaluation of Jatropha curcas L (Euphorbiaceae) Leaves Acute and Subacute Toxicity in Mice - Sawadogo, S.; Sanou, S. D.; Dabiré, A. P.; Belemtougri, G. R.; Sawadogo, L.; Leiris, J. de; Tanguy, S.; Boucher, F. (Journal of Scientific Research, 2018)
Jatropha curcas is a medicinal plant whose dead leaves are particularly used in arterial hypertension and diabetes treatment. The purpose of this study is to conduct an acute and subacute toxicity study of Jatropha curcas leaves aqueous extract (JCLAE) using OECD method. For acute toxicity, dose limits of 2000 and 5000 mg/kg were used. In subacute toxicity study 4 batches were constituted including a control batch that received distilled water for 28 days and the other 3 batches, JCLAE doses of respectively 200, 400, 800 mg/kg for the same duration. The LD50 was determined and the hematological, biochemical and histological parameters were analyzed in mice. The LD50 is greater than 5000 mg/kg. HDL-C is the only biochemical parameter that has experienced significant rise variation. Hematological analysis showed a decrease in mean platelet volume and Platelets number. The histological study revealed cases of hepatic cellular apoptosis and kidneys tubular necrosis among animals treated with highest dose. JCLAE is less toxic than Jatropha curcas leaves aqueous extract and high-dose JCLAE also has a moderate toxic effect on thrombocyte line and a protective effect on cardiovascular system.